2021
DOI: 10.3390/genes12030381
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Plant Sex Chromosomes Highlighted through Advances in Genome Sequencing

Abstract: For centuries, scientists have been intrigued by the origin of dioecy in plants, characterizing sex-specific development, uncovering cytological differences between the sexes, and developing theoretical models. Through the invention and continued improvements in genomic technologies, we have truly begun to unlock the genetic basis of dioecy in many species. Here we broadly review the advances in research on dioecy and sex chromosomes. We start by first discussing the early works that built the foundation for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 222 publications
(306 reference statements)
0
15
0
Order By: Relevance
“…The most similar is Populus alba with ZW sex determination and a 69 kb SDR with 12 W-specific genes ( Yang et al 2021 ), compared to 31 kb and 5 W-specific genes in F. chiloensis . The ability to obtain high-quality chromosome-scale genome assemblies is poised to greatly accelerate the characterization of sex chromosomes ( Carey et al 2021 ), and will clarify whether the features of SDR translocation observed here are general phenomena for plants. Acquisition of haplotype-resolved assemblies, even partially phased such as in this study, will allow a better understanding of autosomal haplotype divergence (exacerbated by repeat sequences), and how this shapes the origin of sex chromosomes.…”
Section: Resultsmentioning
confidence: 94%
“…The most similar is Populus alba with ZW sex determination and a 69 kb SDR with 12 W-specific genes ( Yang et al 2021 ), compared to 31 kb and 5 W-specific genes in F. chiloensis . The ability to obtain high-quality chromosome-scale genome assemblies is poised to greatly accelerate the characterization of sex chromosomes ( Carey et al 2021 ), and will clarify whether the features of SDR translocation observed here are general phenomena for plants. Acquisition of haplotype-resolved assemblies, even partially phased such as in this study, will allow a better understanding of autosomal haplotype divergence (exacerbated by repeat sequences), and how this shapes the origin of sex chromosomes.…”
Section: Resultsmentioning
confidence: 94%
“…The rapid development of high-throughput sequencing techniques has enabled a full flourish of plant genomics. Sexdetermining genes have been identified based on combined genomic and experimental approaches in certain dioecious plants with both Type I and II flowers (Carey et al, 2021;Renner and Müller, 2022). Taken together, these findings make it possible for us to elucidate the mechanism of sex determination in dioecious plants.…”
Section: Introductionmentioning
confidence: 93%
“…Contrastingly, a few systems have strong evidence of a single gene initiating female versus male development, as shown in persimmons and poplars [ 103 , 104 ]. Complementary to the many independent evolutions of dioecy, in each of these species examined, different genes have been identified as sex-determining and they function at varying parts of floral development (see reviews in [ 43 , 105 ]). Studies of additional independent origins of sex chromosomes in plants may indeed identify more novel genes involved in carpel and stamen pathways.…”
Section: The Prismatic Sex Chromosomes Of Plantsmentioning
confidence: 99%